Anomalously polarised emission from a MoS2/WS2 heterostructure. Issue 19 (1st September 2021) - Mol, P. Riya; Barman, Prahalad Kanti; Sarma, Prasad V.; Kumar, Abhishek S.; Sahu, Satyam; Shaijumon, Manikoth M.; Kini, Rajeev N.
Abstract : The brightening of a dark exciton state in the MoS2 layer due to doping and charge transfer from WS2 to this dark state gives rise to circularly polarized emission, from a MoS2 /WS2 heterostructure, with helicity opposite to that of the excitation. Abstract : We report circularly polarised emission, with helicity opposite to the optical excitation, from a van der Waals heterostructure (HS) consisting of a monolayer MoS2 and three-layer WS2 . Selective excitation of the MoS2 layer confirms that this cross-polarized emission is due to the charge transfer from the WS2 layers to the MoS2 layer. We propose that the high levels of n-doping in the constituent layers due to sulphur vacancies and defects give rise to an enhanced transition rate of electrons from the k valley of WS2 to the k ′ valley of MoS2, which leads to the emission, counter polarized to the excitation. Simulations based on the rate equation model support this conclusion.